Récit en mouvement : la construction d’un territoire paysan à Rio Bonito do Iguaçu au Brésil - Mathilde Teixeira Col (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In the context of the socio-environmental crisis we are currently undergoing, it is inevitable that we rethink our ways of inhabiting territories in order to break with the dominant logic of monopolization and abusive exploitation of the Earth’s resources. In Brazil, a country where land inequalities are structural, the peasant movement of the « landless » is the protagonist of the struggle for agrarian reform, in favor of social and environmental justice. This field notebook focuses on the construction of a peasant territory born out of a collective vision, located in Rio Bonito do Iguaçu, in the center-west of Paraná, Brazil. This article presents this territory and the local ways of living through a moving narrative. Based on a field survey conducted from March 2nd to March 5th, 2020, this presentation is part of a thesis on the perspective of autonomy through the collective construction of this territory.